Development of an Interactive Digital Book of Bilingual Children's Stories Based on Local Wisdom in Revitalising Mandailing Batak Language for the Alpha Generation - Asri Yulianda; Harahap, Anna Leli; Rahmad Aditiya; Ritonga, Faridah (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
The background of the problem consists of in the digital era which is more dominated by gadgets causing the alpha generation to be less social, interact and not care about the surrounding environment, especially in local wisdom and Mandailing Batak Language, the lack of children's concern for this can make Mandailing Batak language endangered. The main purpose of this research is to preserve local wisdom and improve regional language skills, especially Mandailing Batak regional language. The research method uses the ADDIE model, namely analysis, design, development, implementation, evaluation. The number of subjects in this study was 20 fifth grade students. The analysis technique used is a Likert scale and the data evaluation tool used uses a questionnaire sheet and the N-Gain Score Test. Based on the results obtained from material experts 95%, media experts 91.66%, linguists 96.66% and teacher responses 95.83%. After testing on students to see the results of the N-Gain test, the average value of the pretest was 74.05 while the average value of the posttest was 94.25. And the N-Gain value is obtained 79.01 which shows in the Effective category.